Influence of investment policy on financial safety of the state in context of balancing - Sytnyk, Natalia; Gerasymenko, Olena (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
Financial safety of the state, being component part of its economic security, defines a condition of security of the state in financial sphere from influence of the various threats caused by insufficiency and disbalance of financial resources. Using regulation actions, the state influences on an investment component of financial safety for the purpose of an effective reconstruction of economy and support of desirable economic growth. Research objective is consideration of interrelation of an investment policy and financial safety of the state. Descriptions and threats of investment component of financial safety of the state are considered. Influence of an aforementioned component on the balancing level of the financial system of the state as one of indicators of safety of finance in Ukraine is researched. For support of investment component of financial safety on a due level it is necessary: to create the proper financial terms for providing of the regular investing of innovative projects; to modify the structure of economy of country for passing to the release of high technology innovative products; to provide functioning legislatively-legal mechanisms of protection of rights of domestic and foreign investors; to create economic terms for investing of modernization and innovative piling up of the fixed assets; to form the system of insurance of investment activity. Providing proper level of financial safety of state is possible on condition of complex approach in relation to determination of reasons of the negative phenomena of its basic components. And by means of correction of negative influences it is possible to define positive processes in the financial system of the state and safety of its finance. It will be difficult to provide the balanced development of the state without levelling of the found out threats.
Keywords: investment policy; balancing; financial safety; investments